Diet and Physical Activity Among Gallstone Patients - Ahmad, Ayesha; Khan, Muhammad Arif; Khalid, Sidra; Bhatti, Qurat-ul-Ain; Yousaf, Riffat; Kaleem, Aisha (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2021)
Gallstones disease has become the most common disease now a days. The dietary factor and physical activity plays an important role in the development of gallstones. These were the major risk factor in gallstones. Objective: The aim of the study is to find the linked between dietary habits and physical activity with gallstones Methods: It was a cross-sectional study conducted at Sir Ganda Ram hospital and Mayo hospital by including 100 patients in 4 months. Mostly the patients were above 30 years of age.Results: 56% males and females had more than 200mg/dl of cholesterol level, majority of males and females did not do indoor exercise that was 59%, 63% of males and females walk less than 30 minutes and 55% of males and females did not climb stairs and 72% males and females had sedentary lifestyle. 70% males and females eat outside only on weekend and holidays, 91% males and females eat fatty food and 78% males and females eat junk food and Results of current study 85% males and females eat 1 cup of sweets, 48% males and females take 1 piece of white bread and 95% males and females drinks 1 cup of whole milk Conclusion: Increased cholesterol level and sedentary lifestyle were increasing the incidence of the gallstones. Refined foods, junk foods and fried foods replaced healthy food which was the major cause of gallstones.